PENYULUHAN KESEHATAN MENGENAI PENTINGNYA PERILAKU HIDUP BERSIH DAN SEHAT (PHBS) DI PANTI ASUHAN TANJUNG BARAT - Anisa Afianti Nur; Raden Roro Kirani Annisa Anjani; Ahmad Mufazzal Marga; Dhanifa Aldeana Maheswari; Annisa Anindita Rahmania; Putri Regita Miolda; Syafira Ratu Fauzi; Alisya Isma Anindita; Khairunnisa Hasan; Celika Fahrudina; Adella Delisa Putri; Keren Stelin Maliangkay; Agnes Gonxa Mulia Hera; Resa Listiani; Hafidz Alfarisi; Syalisa Syabil; Endah Pravita Putri Aldia Pratama; Salwa Salsabil; Prasetio Hadi Pratama; Alya Diah Ullhaque; Afif Amir Amrullah (COVIT (Community Service of Health), 2022)
Clean and Healthy Living Behavior is a behavior that is carried out on the awareness of oneself, family, group, or community as a result of learning so that they can help themselves in realizing public health. There are 10 indicators set, namely the use of clean water, washing hands with clean water and soap, eradicating mosquito nests, using healthy latrines, not smoking, carrying out physical activities, eating fruit and vegetables, weighing toddlers every month, giving exclusive breastfeeding and giving birth. facilities in achieving optimal health status. Therefore, counseling regarding a Clean and Healthy Lifestyle was carried out to the children of the Tanjung Barat orphanage with the aim that the children were able to create a healthy environment, prevent the spread of disease, be able to take advantage of health facility services, and be able to develop health that comes from the community. The community service method carried out is to give a pretest to the children of the Tanjung Barat orphanage to measure their knowledge of Clean and Healthy Life Behavior, followed by the delivery of material on Clean and Healthy Life Behavior, and after that, a post-test is given to determine understanding children to the material provided. The results of the pre-test showed that the average target knowledge was 92.14. Then, there was an increase in post-test results of 99.29. So this article concludes that there is an increase in children's knowledge about Clean and Healthy Life Behavior. Thus, Giving Counseling to Students About Clean and Healthy Life Behavior is Very Effective. Keywords: Clean and Healthy Life Behavior, Children, Counseling, Orphanage